Polysaccharide based superabsorbent hydrogel from Mimosa pudica: swelling–deswelling and drug release. Issue 28 (29th February 2016) - Muhammad, Gulzar; Hussain, Muhammad Ajaz; Ashraf, Muhammad Umer; Haseeb, Muhammad Tahir; Hussain, Syed Zajif; Hussain, Irshad
Abstract : Polysaccharide based stimuli responsive, superporous and superabsorbent hydrogel for sustained drug release. Abstract : Herein, we have evaluated a polysaccharide, glucuronoxylan, isolated from the seeds of Mimosa pudica (MP) for its water holding capacity, pH and salt responsive swelling–deswelling behavior, and sustained drug release. The MP hydrogel (MPH) has shown a high water retention capacity. The MPH exhibited negligible swelling at pH 1.2 while high swelling was observed at pH 6.8, 7.4 and in deionized water which follows second order kinetics, whereas the MPH deswells in NaCl and KCl solutions and ethanol. The presence of interconnected macropores with an average diameter of 62.94 μm was revealed using scanning electron microscopy (SEM) of a swollen then freeze dried sample of MPH. Furthermore, the MPH was explored as a sustained release material for a tablet formulation of diclofenac sodium. The drug release mechanism from the MPH containing tablet formulation was found to be super case-II transport. The results have indicated that the MPH could be a potential candidate for sustained release formulations.